Multiple small bowel GIST as GI manifestation of neurofibromatosis type I: A case report - Habtamu Tsegaye; Adamu Tigabu (Radiology Case Reports)
Neurofibromatosis type 1 (NF1) is characterized by café-au-lait patches on the skin and the presence of neurofibromas. Gastrointestinal stromal tumor (GIST) is the most common GI tumour in NF1 patients. In NF1-associated GIST, KIT and PDGFRA mutations are frequently absent and imatinib is ineffective. Surgical resection is first-line treatment. A 58-year-old woman present with dyspepsia symptoms and physical examination was notable for multiple café-au-lait patches and multiple subcutaneous nodular masses of the skin of the face, trunk, and limbs. Abdomininoplevic CT shows multiple different size avidly enhancing small bowel mass. The patient underwent laparotomy and resection with jejenu-jejunal anastomosis was done with smooth post op condition. Histopathology shows Grade I GIST with score 4+ immune reactivity for CD117. It is typically difficult to make a conclusive preoperative diagnosis of GISTs. Computed tomography of the abdomen should be done in Neurofibromatosis type 1 Patients with gastrointestinal symptoms as GISTs may be the cause of these symptoms. Surgical resection may also be performed for both diagnosis and treatment. The objective of this case repot is to describe the radiological feature of multiple GIST in elder NF1 patient in resource limited setup.